2022
DOI: 10.1080/17452759.2022.2155197
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous microstructure and mechanical behaviour of Al-8.3Fe-1.3V-1.8Si alloy produced by laser powder bed fusion

Abstract: The relationship between processing parameters, microstructure, and mechanical properties of Al-8.3Fe-1.3V-1.8Si alloy processed by laser powder bed fusion is seldom studied. Therefore, fully dense alloys with two parameters were selected to investigate this key issue. The results show that the alloy with low power and scanning speed (S200) shows fan-shell-shaped melt pools and laser tracks while another (S350) shows a deeper and wider melt pool. Both alloys obtain a heterogeneous microstructure without a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 99 publications
(86 reference statements)
0
0
0
Order By: Relevance
“…The content of magnetic particles determines the saturation magnetization in the composites. [ 18a ] The act of external magnetic field on the magnetic particles polarize them, forming magnetic dipoles. [ 30 ] The presence of dipoles resulted in attraction among particles, consequently leading to the formation of magnetic chains and the reduction of inter‐particle distances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of magnetic particles determines the saturation magnetization in the composites. [ 18a ] The act of external magnetic field on the magnetic particles polarize them, forming magnetic dipoles. [ 30 ] The presence of dipoles resulted in attraction among particles, consequently leading to the formation of magnetic chains and the reduction of inter‐particle distances.…”
Section: Resultsmentioning
confidence: 99%
“…The stiffness and hardness in the aligned direction were increased by 29% and 23% compared with the vertical direction, respectively. It also demonstrated that MF‐DLP 4D printing technique could significantly improve the wear resistance and magnetic stimuli‐response behavior of magnetic composites in the aligned direction, [ 18 ] showing effective enhancement of functionality through manipulation of the magnetic particles during 4D printing. Some challenges remain on the MF‐DLP fabricated smart materials by remote control of the actuators using electrical and magnetic fields simultaneously or sequentially.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xie et al 19 reported that befitting overlap region widths (ORWs) could improve the densification degree and guarantee metallurgical quality. Yu et al 20 demonstrated that the microstructure and mechanical properties of SLM-built alloy can be effectively controlled by adjusting processing parameters. Gatta et al 21 identified that the feasibility of the SLM process that fabricated a customised Al–Cu–Mg–Si alloy, and the optimised process parameters can obtain the maximum relative density of 97%.…”
Section: Introductionmentioning
confidence: 99%